Opinions on Qualifications of Surveyors of Care for Children with Disabilities in Japan - Horiguchi, Toshihiro; Uchiyama, Tokio; Ozawa, Atsushi; Matsubasa, Tadashi; Watanabe, Kenichirou; Adachi, Jun; Inada, Naoko (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Retraction Notice: The article titled "Opinions on Qualifications of Surveyors of Care for Children with Disabilities in Japan" by Horiguchi T, Uchiyama T, et al., published in 2021 (Vol. 9, pp. 82-89), has been retracted at the request of the authors and the President of the National Center of Neurology and Psychiatry (NCNP). The decision to retract the article follows an investigation by the Research Code of Conduct Committee, which identified ethical violations related to the conduct of the research. We sincerely apologize to the readers and the academic community for any inconvenience caused by this issue. For more details on the reason for the retraction, please see the links below to the letter and investigation report from the concerned departments.